2010
DOI: 10.1186/1479-5868-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Trend in active transportation to school among Swiss school children and its associated factors: three cross-sectional surveys 1994, 2000 and 2005

Abstract: BackgroundGiving the rising trend in childhood obesity in many countries including Switzerland, strategies to increase physical activity such as promoting active school travel are important. Yet, little is known about time trends of active commuting in Swiss schoolchildren and factors associated with changes in walking and biking to school.MethodsBetween 1994 and 2005, information about mobility behaviour of children aged 6-14 years was collected within three Swiss population based national travel behaviour su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 17 publications
8
93
1
3
Order By: Relevance
“…Similarly, other European studies (Sere et al, 2008;Borrestad et al, 2011;Bringolf Isler et al, 2008;Chillon et aL, 2009) on urban areas also showed considerably higher prevalence of active commuting (65 to 88%) than in our study. Thus, rural urban differ ences may explain the discrepancies in prevalence of active commut ing to schooL Representative studies showed that 71.4% of school children in Switzerland and 12.9% of students in the United States were active commuters (Grize et al, 2010;McDonald, 2007). Approximately 20% of secondary school students were active commuters to and 30% from school in Ontario (Canada) and in Australia (van der Ploeg et al, 2008;Wong et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other European studies (Sere et al, 2008;Borrestad et al, 2011;Bringolf Isler et al, 2008;Chillon et aL, 2009) on urban areas also showed considerably higher prevalence of active commuting (65 to 88%) than in our study. Thus, rural urban differ ences may explain the discrepancies in prevalence of active commut ing to schooL Representative studies showed that 71.4% of school children in Switzerland and 12.9% of students in the United States were active commuters (Grize et al, 2010;McDonald, 2007). Approximately 20% of secondary school students were active commuters to and 30% from school in Ontario (Canada) and in Australia (van der Ploeg et al, 2008;Wong et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…States, 131 Switzerland, 132 and Canada. 133 A review focusing on different domains of activity concluded that the available evidence does not support the notion that overall physical activity levels and sport participation have declined recently in youth.…”
Section: Time Trends In Physical Activity Practicementioning
confidence: 99%
“…4 Within the context of the nutrition and PA transition, 6 in which PA patterns are often the result of environmental and societal changes, it is important to understand the role of activities that can be incorporated into everyday life, including active school transport (AST).The prevalence of AST, unfortunately, has declined in several HIC including Canada, 7 the United States, 8 Australia 9 and Switzerland. 10 In LMIC the data are limited, but studies conducted in Brazil, China, Mozambique and Vietnam have also shown that the AST trend in this countries mirrored HIC trends. [11][12][13][14] Active travel to school is one way in which children can increase their levels of PA and prevent obesity.…”
Section: Introductionmentioning
confidence: 99%